Neurological complications - Law, Meng (Cancer imaging, 2009)
Patients with neurological malignancies are subject to developing a unique set of complications that require emergent evaluation and treatment. With the increasing incidence of cancer in the general population and improved survival, these emergencies will be more frequently encountered. Physicians must be able to recognize these conditions and institute appropriate therapy after a focused initial evaluation. The approach to definitive therapy is commonly multidisciplinary, involving surgeons, radiation oncologists, medical oncologists, and other medical specialists. Prompt interventions can be lifesaving and may spare patients considerable morbidity and pain. In neuro-oncology, there are some more specific complications and emergencies. The more general complications are not reviewed here.